Attempted synthesis of central furopyran core of diocollettines A via a gold-catalyzed cascade 1,6-diyne cycloisomerization process - Mullapudi, Venkannababu; Ramana, V, Chepuri (Tetrahedron Letters, 2020)
Herein, we describe an Au-catalyzed cascade diyne cycloisomerization process that was projected to construct the central furopyran bicyclic core of Diocollettines A. Our intended strategy for the annulation of the third thf ring is based on epoxidation and subsequent intramolecular acetalization. However, the initial alkynol cyclization occurred in an undesired 5-exo-dig mode, ultimately leading to an undesired furopyran. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: 1; 6-Hexadiyne; Alkynol cycloisomerization; Diocollettines A; Gold-catalysis; Total synthesis